4 Experiencing Social Change: Life during the Mimbres Classic Transformation. Issue 1 (16th May 2016) - Hegmon, Michelle; Nelson, Margaret C.; Schollmeyer, Karen Gust
ABSTRACT: What was it like to live during a time of social transformation? To live during the culture changes and depopulation at the end of the Classic Mimbres period, ca. 1130 C.E.? As part of the Archaeology of the Human Experience we address these questions with an evidence‐based account of what people did and how the changes affected their lives. Where possible and reasonable, we make people the subjects of our sentences. This approach leads to the conclusions that most changes—such as the end of a land tenure system—affected different people in different ways. The approach also raises questions about what happened to the artists when their artistic tradition ended .